Torsion of left main bronchus during general anesthesia for posterior instrumented spinal fusion. Issue 7 (25th May 2016) - Arumainathan, Renuka; Morris, Stephen A. C.; George, Marina
Key Clinical Message: Pulmonary function tests such as flow‐volume loops and reconstructive radiological imaging may aid the detection of large airway obstruction prior to corrective surgery for severe scoliosis. Intraoperative use of halo‐gravity traction may help to reduce the severity of the scoliosis, and thus the extrinsic compression or torsion of the airways. Abstract : Pulmonary function tests such as flow‐volume loops and reconstructive radiological imaging may aid the detection of large airway obstruction prior to corrective surgery for severe scoliosis. Intraoperative use of halo‐gravity traction may help to reduce the severity of the scoliosis, and thus the extrinsic compression or torsion of the airways.